Mathematical communication skills in the context of linear equations: A study on students' proficiency and self-esteem - Kuncoro, Krida Singgih; Kusumaningrum, Betty; Agustito, Denik; Meirani, Fajar; Lestari, Ega Sri (Psychology, Evaluation, and Technology in Educational Research, 2023)
This research aimed to analyze the mathematical communication skills of eighth-grade students in junior high school regarding the topic of linear equations. The population of this study consisted of eighth-grade students in one of the schools in Yogyakarta. Prior to selecting the subjects, a self-esteem questionnaire was administered, and then 6 students were randomly chosen, with 3 students having high self-esteem and 3 students having medium self-esteem. The selected students were then given a written test on mathematical communication skills and an interview. The data collected for this study included the results of the written test and the interviews. Based on the data analysis conducted, it was found that among the six selected students, SP1 was able to answer the questions using written text, drawing, and mathematical expressions, but their communication of the answers was not accurate. SP2 exhibited higher mathematical communication skills compared to the other subjects. SP3 had low mathematical communication skills, SP4 had moderate communication skills, SP5 had low mathematical communication skills, and SP6 could be considered to have moderate communication skills. Therefore, it is expected that teachers can provide students with the freedom to solve problems according to their own understanding and ideas.